SARS-CoV-2 spike protein S1 subunit induces potent neutralizing responses in mice and is effective against Delta and Omicron variants - Mamedov, Tarlan; Yuksel, Damla; Gurbuzaslan, Irem; Gulec, Burcu; Mammadova, Gulshan; Ozdarendeli, Aykut; Pavel, Shaikh Terkis Islam; Yetiskin, Hazel; Kaplan, Busra; Uygut, Muhammet Ali; Hasanova, Gulnara (Frontiers in Plant Science, 2023)
SARS-CoV-2, the virus responsible for the COVID-19 pandemic, belongs to the betacoronavirus genus. This virus has a high mutation rate, which rapidly evolves into new variants with different properties, such as increased transmissibility or immune evasion. Currently, the most prevalent global SARS-CoV-2 variant is Omicron, which is more transmissible than previous variants. Current available vaccines may be less effective against some currently existing SARS-CoV-2 variants, including the Omicron variant. The S1 subunit of the spike protein of SARS-CoV-2 has been a major target for COVID-19 vaccine development. It plays a crucial role in the virus’s entry into host cells and is the primary target for neutralizing antibodies. In this study, the S1 subunit of the spike protein of SARS-CoV-2 was engineered and produced at high level in Nicotiana benthamiana plant. The expression level of recombinant S1 protein was greater than 0.5 g/kg fresh weight and the purification yield was at least ~0.3 g of pure protein/kg of plant biomass, which would make of a plant produced S1 antigen an ideal vaccine candidate for commercialization. Purified, the plant produced SARS-CoV-2 S1 protein exhibited significantly higher binding to the SARS-CoV-2 receptor, angiotensin converting enzyme 2 (ACE2). Moreover, we also show that recombinant S1 protein/antigen-elicited antibodies can neutralize the Delta or Omicron variants. Collectively, our results demonstrate that a plant-produced S1 antigen could be a promising vaccine candidate against SARS-CoV-2 variants including Omicron.